The European Vector of Italy’s Foreign Policy - S. M. Gavrilova (Проблемы постсоветского пространства)
The foreign policy of the Italian Republic is implemented in three key areas: European, Atlantic and Mediterranean. This article examines the European vector of Italian politics, the characteristic features of this direction and its evolution in the XX–XXI centuries. The Italian Republic has played a significant role in the process of European integration, taking an active part in all key initiatives of this process since the 1960s. In the second half of the XX — early XXI centuries european policy has become a tool for Italy to strengthen its own status in the international arena, and an active position in the integration processes is a way to stand on a par with the leaders of the European space. It is Europeanism, along with Atlanticism, that became the basis of the foreign policy concept of Italy in the second half of the XX century and determines the political image of the country and its position in the international arena. In this context, it is especially important that the foreign policy dimension of Italian politics is closely linked to the domestic political situation in the country. At the beginning of the XXI century, there are outbursts of euroscepticism in the country associated with the problem of migration and dissatisfaction with supranational authorities in times of crisis, such as COVID-19. Europeanism, however, remains a key dimension of the country’s foreign policy.